THE POSSIBLE DETECTION OF A BINARY COMPANION TO A TYPE IBN SUPERNOVA PROGENITOR - Maund, J. R.; Pastorello, A.; Mattila, S.; Itagaki, K.; Boles, T. (The Astrophysical journal, 2016)
ABSTRACT We present late-time observations of the site of the Type Ibn supernova (SN) 2006jc, acquired with the Hubble Space Telescope Advanced Camera for Surveys. A faint blue source is recovered at the SN position, with brightness , and mag, although there is no detection in a contemporaneous narrow-band image. The spectral energy distribution of the late-time source is well-fit by a stellar-like spectrum ( and ), subject to only a small degree of reddening-consistent with that estimated for SN 2006jc itself at early-times. The lack of further outbursts after the explosion of SN 2006jc suggests that the precursor outburst originated from the progenitor. The possibility of the source being a compact host cluster is ruled out on the basis of the source's faintness; however, the possibility that the late-time source may be an unresolved light echo originating in a shell or sphere of pre-SN dust (within a radius ) is also discussed. Irrespective of the nature of the late-time source, these observations rule out a luminous blue variable as a companion to the progenitor of SN 2006jc.